The impact of HIV/AIDS stigma on HIV counseling and testing in a high HIV prevalence population in Uganda - Ayiga, N.; Nambooze, H.; Nalugo, S.; Kaye, D.; Katamba, A. (African health sciences, 2013)
Background: Despite its importance in HIV/AIDS prevention and treatment, HIV/AIDS Counseling and Testing (HCT) is low in sub-Saharan Africa, where the disease continues to be a serious public health problem. This has in part been attributed to HIV/AIDS related stigma. Objective: To assess the level of HIV/AIDS related stigma and its impact on uptake of HCT in a high HIV prevalence population in Uganda. Methods: The paper used cross-sectional data on 135 men and 185 women in reproductive ages. Data were analyzed using the Pearson’s chi-square statistic and the random intercept binary logistic regression model to identify significant predictors of uptake of HCT. Results: The result shows that only 18.4% of the respondents, most of them men expressed highly stigmatizing attitudes against PLHA and 59%, men and women alike, received HCT. Uptake of HCT was higher among men (OR=1.89, p<0.01) and women (OR=4.48, p <0.001) who expressed least stigmatizing attitudes. Secondary/higher education, work in the informal sector and being ever married were significant predictors of uptake of HCT. Compared to men, women aged 25- 34, 35+ and with one sexual partner were more likely to have received HCT. Conclusions: The low level of stigma, older age, higher level of education, being ever married and monogamous sexual relationships are significant predictors of increased uptake of HCT.
Keywords: HIV counseling; Testing; Stigma